Enhancement of Photocatalytic Decolorization of Methylene Blue Over WO3/CNT Incorporated TiO2 Nanocatalysts Under UV Light Radiation - Zhu, Lei; Meng, Ze-Da; Cho, Kwang-Youn; Ghosh, Trisha; Oh, Won-Chun (Asian Journal of Chemistry, 2012)
The photodegradation of methylene blue solution catalyzed by anatase TiO2 and composite photocatalysts: WO3/TiO2, WO3/CNT/TiO2 (with different content of W) was studied under irradiation with UV light. The catalysts were characterized by SEM, TEM, BET, XRD, EDX and UV-VIS absorption spectroscopy. The results showed that MWCNTs used as supports materials efficiently inhibit the agglomeration of WO3/TiO2 and improve the dispersion of nanoparticles. The photoactivity of the prepared materials under UV irradiation was tested using the conversion of methylene blue in aqueous solution. In comparison with non-nanocarbon supported WO3/TiO2 composites, the nanocarbon supported WO3/TiO2 composites had higher absorption ability with a larger specific surface area and showed higher photocatalytic activity of degradation methylene blue solution under UV light irradiation, meanwhile it was found that an optimal WO3 dosage of 8.80 wt % in WO3/CNT/TiO2 composite achieved the highest photodegradation rate in this study. It can be considered that the methylene blue removal effect of the WO3/CNT/TiO2 composite is affected by two kinds of effects: adsorption effect by MWCNTs and photoctalytic effect by TiO2. Finally, the reasons for the obvious increase of photocatalytic activity indicated that the effect of MWCNTs, which could absorb UV light to create photoinduced electrons (e–) and the electron trapping effect of WO3, which resulted in the recombination rate of electrons/holes in WO3/CNT/TiO2 declined.